A privacy paradox: the power of technological surveillance and Its effect on information technology usage behavior - Rençberoğlu, Emre. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
Thanks to developing technologies, reaching information has become easier and the big data concept started to be used in various fields. Today, almost all of the technologies which are used widely, such as the internet, mobile phones, computers and smart TVs, are capable of collecting and storing data. The data gathering activity is a routine process for almost all private companies and governments, which can result in incidents of exploitation and misuse. Moreover, some sociological impacts, which include self-censorship and changing perceptions, are considered one of the results of increasing information privacy concerns. The aim of this thesis is to contribute to the literature by investigating the multidimensionality of information privacy concerns. For this purpose, a survey was conducted with 641 participants to measure the relationship between information privacy concerns with regard to news, regulations, user agreements, public beliefs and perceptions. Additionally, the association between information technology (IT) usage behavior and the dimensions of the information privacy concerns are examined. According to the analysis of survey data, demographic differences are important in terms of privacy concerns. News and regulations are highly associated with privacy concerns, but security perception is only related to the data collection dimension. Another finding of the research is that there is not a significant relationship between the information privacy concerns and IT usage behavior, except general IT tools.
Keywords: Electronic surveillance.; Privacy, Right of.